ANALISIS ALIRAN DUA FASA PADA SMALL TUBE LIQUID-LIFTING TECHNIQUE (STLT) UNTUK PENANGGULANGAN LIQUID LOADING - Yanuar Firdaus, Muhammad
Liquid loading is serious problem that occur on gas well, where well are filled with liquid that inhibit the movement of gas futhermore the presence of liquid causes gas well drawdown dropped. This liquid comes from aquifer, water formation, vapor condensate and hidrocarbon condensate. This liquid not lifted towards surface facility because wells energy decreased after long production. Deliquification method is the method used to overcome liquid loading problem. Deliquification means removing the accumulated liquid from the bottom of the well. the current methods of deliquification that has been widely used for example swabbing, plunger lift, velocity string, modissied ESP, foam etc. Small tube velocity strings utilize gas velocity through small tubing to remove liquid in the bottom of the well. Through laboratory studies showed that the use of small tube can remove fluid from the bottom of the well up to 14.09 bpd using 9.6 mm pipeline and up to 4 bpd using 4.65 mm pipeline with a pressure gradient of 0.2667 psi / ft. Laboratory study was conducted using a pipe with a length of 8m as the sample tubing and nitrogen gas as a source of pressure. Through calculation of Hasan Kabir method, produced gas through small tubes can be calculated at a certain pressure.